The triple-dip La Niña of 2020–22: updates to the correlation of ENSO with the termination of solar cycles - Leamon, Robert J. (Frontiers in Earth Science, 2023)
The Sun provides the energy required to sustain life on Earth and drive our planet's atmosphere.However, establishing a solid physical connection between solar and tropospheric variability has posed a considerable challenge across the spectrum of Earth-system science. Over the past few years a new picture to describe solar variability has developed, based on observing, understanding and tracing the progression, interaction and intrinsic variability of the magnetized activity bands that belong to the Sun's 22-year magnetic activity cycle. A solar cycle's fiducial clock does not run from the canonical min or max, instead resetting when all old cycle polarity magnetic flux is cancelled at the equator, an event dubbed the "termination" of that solar cycle, or terminator. In a recent paper, we demonstrated with high statistical significance, a correlation between the occurrence of termination of the last five solar cycles and the transition from El Niño to La Niña in the Pacific Ocean, and predicted that there would be a transition to La Niña in mid 2020. La Niña did indeed begin in mid-2020, and endured into 2023 as a rare "triple dip" event, but some of the solar predictions made did not occur until late 2021. This work examines what went right, what went wrong, the correlations between El Niño, La Niña and geomagnetic activity indices, and what might be expected for the general trends of large-scale global climate in the next decade.